Pelayanan Gereja di Tengah Dunia: Tegangan Antara Pelayanan Karitatif?Reformatif dan Transformatif - Silvester Manca (STIPAS St. Sirilus Ruteng, 2020)
In this articel, the author to emphasize the importance of paying attention to the tension between deaconia/charity service and transformative service in the church. While observing this tension, the church today is urged to implement transformative deaconia. The urged is certainly based on the context of human life which is on colored by so much suffering which is quite a lot cause by social, cultural and economic system and structures that are unjust. In that context, the diaconia of the church does not only stop at the caracter deaconia, but must show a transformative character.